The Influence of Parenting Styles and Managerial Elements on School Readiness in Kindergarten-Aged Children within a Community - Andi Adawiah; Asmini Asmini; Akmal Umar; Wamaungo Juma Abdu (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Humanity's phase-to-phase development necessitates adept management, crucial for community growth. Employing a quantitative research approach, this study investigates how familial managerial elements impact children's early school readiness. It scrutinizes two aspects: the influence of variables on parenting style within families and parenting style's impact on school readiness. Key variables include parents’ managerial perception, family socioeconomic status, and family involvement in kindergarten programs. Quantitative methods, encompassing statistical tests and SPSS analysis, meticulously explore the relationships and influences among these variables, unveiling significant effects. Importantly, parental managerial perception positively affects parenting style, socioeconomic status, and family involvement in kindergarten programs, quantitatively highlighting managerial elements' impact on child development. Furthermore, a management-focused parenting style demonstrates a direct and positive quantitative influence on children's school readiness. These findings underscore the significance of considering managerial aspects in families as pivotal contributors to children's educational outcomes. This rigorous quantitative approach enriches our comprehension of these influences and informs policies and interventions, enhancing school readiness and community development.